A cross-sectional pilot study of antibiotic resistance in Propionibacterium acnes strains in Indian acne patients using 16s-RNA polymerase chain reaction: A comparison among treatment modalities including antibiotics, benzoyl peroxide, and isotretinoin - Kabir Sardana; Tanvi Gupta; Bipul Kumar; Hemant K Gautam; Vijay K Garg (Wolters Kluwer Medknow Publications, 2016)
Background: Antibiotic resistance is a worldwide problem in acne patients due to regional prescription practices, patient compliance, and genomic variability in Propionibacterium acnes, though the effect of treatment on the resistance has not been comprehensively analyzed. Aims: Our primary objective was to assess the level of antibiotic resistance in the Indian patients and to assess whether there was a difference in the resistance across common treatment groups. Subjects and Methods: A cross-sectional, institutional based study was undertaken and three groups of patients were analyzed, treatment naοve, those on antibiotics and patients on benzoyl peroxide (BPO) and/isotretinoin. The follicular content was sampled and the culture was verified with 16S rRNA polymerase chain reaction, genomic sequencing, and pulsed-field gel electrophoresis. Minimum inhibitory concentration (MIC) assessment was done for erythromycin (ERY), azithromycin (AZI), clindamycin (CL), tetracycline (TET), doxycycline (DOX), minocycline (MINO), and levofloxacin (LEVO). The four groups of patients were compared for any difference in the resistant strains. Results: Of the 52 P. acnes strains isolated (80 patients), high resistance was observed to AZI (100%), ERY (98%), CL (90.4%), DOX (44.2%), and TETs (30.8%). Low resistance was observed to MINO (1.9%) and LEVO (9.6%). Statistical difference was seen in the resistance between CL and TETs; DOX/LEVO and DOX/MINO (P < 0.001). High MIC90 (≥256 μg/ml) was seen with CL, macrolides, and TETs; moreover, low MIC90 was observed to DOX (16 μg/ml), MINO (8 μg/ml), and LEVO (4 μg/ml). Though the treatment group with isotretinoin/BPO had the least number of resistant strains there was no statistical difference in the antibiotic resistance among the various groups of patients. Conclusions: High resistance was seen among the P. acnes strains to macrolides-lincosamides (AZI and CL) while MINO and LEVO resistance was low.